FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN KE PUBLIK - Ravanelli, Fais; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test and to find out some factors which influence the timeliness of thesubmission of financial statements of public companies in Indonesia. These factors which have been tested in thisresearch is profitability, liquidity, firm size, and firm age as the independent variables whereas the timeliness asdependent variable. The population has been obtained by using purposive sampling method on the constructioncompanies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods and based on thepredetermined criteria, 30 samples of construction companies. The analysis method has been done by usinglogistic regressions analysis with the instrument is SPSS (Statistical Product and Service Solution). The resultof this research stated that profitability, liquidity, firm size, and firm age do not have any influence to thetimeliness of the submission of financial statements of construction companies which are listed in IndonesiaStock Exchange.Keywords: Punctuality, profitability, liquidity, firm size, firm age.